The Experience in Personal Social Systems Questionnaire (EXIS.pers): Development and Psychometric Properties. Issue 1 (8th February 2016) - Hunger, Christina; Bornhäuser, Annette; Link, Leoni; Geigges, Julian; Voss, Andreas; Weinhold, Jan; Schweitzer, Jochen
Abstract : This study presents the theoretical background, development, and psychometric properties of the German and English versions of the Experience in Personal Social Systems Questionnaire (EXIS.pers). It assesses how the members of a personal social system experience their situation within that system. It is designed as a research tool for interventions in which only one member of the system participates (e.g., Family Constellation Seminars). The EXIS.pers was created to measure change on the individual level relating to one's own important personal social system. In Study 1, we used exploratory factor analysis (EFA) for latent variable identification of the original German EXIS.pers ( n = 179). In Studies 2 and 3, we used confirmatory factor analysis (CFA) to examine the dimensionality of the German ( n = 634) and English ( n = 310) EXIS.pers. Internal consistencies and cross‐cultural structural equivalence were assessed. EFA indicated that a four‐factor model provided best fit for the German EXIS.pers. For both the German and English EXIS.pers, CFA provided the best fit for a five‐factor bi‐level model that included a general factor ( Experience In Personal Social Systems ) and four dimensions ( Belonging, Autonomy, Accord, Confidence ). Good internal consistencies, external associations, and cross‐cultural structural equivalence were demonstrated. This study provides first evidence for the German and English EXIS.pers as an economical and reliable measure of an individual's experience within his or her personal social systems.